Network pharmacology suggests biochemical rationale for treating covid-19 symptoms with a traditional chinese medicine (2020)
hinese herbal formulas including the lung-cleaning and toxicity-excluding (LCTE) soup have played an important role in treating the ongoing COVID-19 pandemic (caused by SARS-CoV2) in China. Applying LCTE outside of China may prove challenging due to the unfamiliar rationale behind its application in terms of Traditional Chinese Medicine. To overcome this barrier, a biochemical understanding of the clinical effects of LCTE is needed. Here, we explore the chemical compounds present in the reported LCTE ingredients and the proteins targeted by these compounds via a network pharmacology analysis. Our results indicate that LCTE contains compounds with the potential to directly inhibit SARS-CoV-2 and inflammation, and that the compound targets proteins highly related to COVID-19’s main symptoms. We predict the general effect of LCTE is to affect the pathways involved in viral and other microbial infections, inflammation/cytokine response, and lung diseases. Our work provides a biochemical basis for using LCTE to treat COVID-19 and its main symptoms.